2004
DOI: 10.1007/s10393-004-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

Control of River Blindness in West Africa: Case History of Biodiversity in a Disease Control Program

Abstract: The elimination of river blindness (onchocerciasis) in West Africa has been one of the most successful public health and economic development programs yet conducted. Control was based on aerial application of insecticides to control the aquatic, larval stages of black flies in the Simulium damnosum complex and distribution of ivermectin-based drugs to reduce incidence of the filarial worm, Onchocerca volvulus, that may ultimately result in blindness. Control efforts were long-term , extensive (with as many as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In West Africa as a whole, little is known about the diversity of aquatic macroinvertebrates (Yaméogo, Resh & Molyneux, ), although several studies have been conducted with benthic macroinvertebrate communities in Côte d'Ivoire. These studies mainly concerned the inventory of macroinvertebrates (Edia et al ., ; Diomandé et al ., ) and the relationships between benthic macroinvertebrate communities and the environmental variables (Bony et al ., ; N'Zi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In West Africa as a whole, little is known about the diversity of aquatic macroinvertebrates (Yaméogo, Resh & Molyneux, ), although several studies have been conducted with benthic macroinvertebrate communities in Côte d'Ivoire. These studies mainly concerned the inventory of macroinvertebrates (Edia et al ., ; Diomandé et al ., ) and the relationships between benthic macroinvertebrate communities and the environmental variables (Bony et al ., ; N'Zi et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Resh and Jackson (1993) observed that species richness measures were sensitive to the impact of human activities on the stream ecosystems, particularly aquatic insects, which can be considered as good biological indicators of stream disturbances (Norris, 1995;Wright et al, 1995). Despite their importance in stream ecosystems, aquatic insects are little studied in West Africa (Yaméogo et al, 2004). In Ivory Coast, only a few studies have been devoted to macroinvertebrate fauna (Dejoux et al, 1981;Sankaré, 1991;Diomandé, 2001;Diétoa, 2002;Edia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For Africa, Fjeldsa (2007) and current co-authors suggest biodiversity needs to be further considered at the local, livelihood and larger ecological scales. Water management is also considered to be critical for disease prevention (Colwell and Wilcox, 2010); for example, concerning river blindness (Yameogo et al, 2004); malaria and yellow fever (Junglen et al, 2009); and African swine fever (Jori and Bastos, 2009). Research has found indications that global climate change could lead to increased rates of cholera in Africa (Paz, 2009), and more generally is expected to be of great significance in lowering food security throughout SSA (Thompson et al, 2010).…”
Section: Kenyamentioning
confidence: 99%